1972
DOI: 10.1111/j.1476-5381.1972.tb08101.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins, oxygen tension and smooth muscle tone

Abstract: Summary1. By using indomethacin to inhibit their intramural synthesis, we have investigated the contribution of prostaglandins to the maintenance of (a) the intrinsic tone of isolated smooth muscle preparations and (b) contractions produced by drugs or high oxygen concentration. 2. When treated with indomethacin, the rat stomach strip and chick rectum preparation slowly relaxed, whether they were bathed in Krebs solution or blood. Although their sensitivity to added prostaglandin was somewhat enhanced, they be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(73 citation statements)
references
References 26 publications
6
67
0
Order By: Relevance
“…Thus, as in other isolated smooth muscles such as the cat iris (Posner, 1970), rabbit jejunum (Ferreira, Herman & Vane, 1972) rat stomach strip and guinea-pig colon (Eckenfels & Vane, 1972) a local prostaglandin production maintains the inherent smooth muscle activity. For the pregnant rat isolated uterus Aiken (1972) has come to a similar conclusion; he further showed that papaverine inhibits spontaneous activity without affecting prostaglandin production, thus eliminating the possibility that prostaglandin release is a consequence of uterine contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as in other isolated smooth muscles such as the cat iris (Posner, 1970), rabbit jejunum (Ferreira, Herman & Vane, 1972) rat stomach strip and guinea-pig colon (Eckenfels & Vane, 1972) a local prostaglandin production maintains the inherent smooth muscle activity. For the pregnant rat isolated uterus Aiken (1972) has come to a similar conclusion; he further showed that papaverine inhibits spontaneous activity without affecting prostaglandin production, thus eliminating the possibility that prostaglandin release is a consequence of uterine contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have previously suggested that endogenous prostaglandins play an important role in the maintenance of tone and the development of spontaneous contractility in the mammalian bladder (Eckenfels & Vane, 1972;Bultitude et al, 1976; domethacin, aspirin and corticosterone. In addition, the cyclo-oxygenase inhibitors also reduced the response to phentolamine in a concentrationdependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The abolition of these changes by incubation with indomethacin suggests that the strips of gall bladder release a prostaglandin-like substance, which in turn affects the tonic and phasic activity of the muscle. other guinea-pig isolated tissues (ileum, Davison et al, 1972;Botting & Salzmann, 1975;trachea, Orehek et al, 1975;taenia coli, Sakato & Shimo, 1976), rabbit jejunum (Ferreira, Herman & Vane, 1972), rat stomach strip and chick rectum (Eckenfels & Vane, 1972). Although a noradrenergic innervation to the guinea-pig gall bladder has been clearly demonstrated (Baumgarten & Lange, 1969;Davison et al, 1978), there have been few studies of the effects of exogenously applied catecholamines on this tissue.…”
Section: Discussionmentioning
confidence: 99%